Breast density estimation on full-field-digital mammography (ffdm) by general radiologists: comparison of bi-rads and tabar classification sytems - Hassan, Radhiana; Ab Rahman, Jamalludin; Zaini, Izwan Zanni; Mohammed Saeed Abdulateef, Reem; Yahaya, Azura Sharena (2014)
Purpose of Study: The aim of the study is to compare inter-observer agreement between general radiologists in classification of mammographic breast density using TABAR’s pattern and BI-RADS classification systems on Full-Field Digital Mammography (FFDM). Materials and Method A 400 data set of mammograms in mediolateral and craniocaudal views was independently evaluated by three radiologists. Breast density was classified using BI-RADS and TABAR classification systems. The three radiologists interpreting the mammogram images were general radiologists with three, four and one years’ experience respectively. There was no special coaching conducted prior to data interpretation. Results: Inter-observer agreement for the BI-RADS are slight to fair (reviewer 1 vs reviewer 2: k=0.19, reviewer 1 vs reviewer 3, k=0.07 and reviewer 2 vs reviewer 3, k=0.49) and for TABAR is fair to moderate (reviewer 1 vs reviewer 2: k=0.23, reviewer1 vs reviewer 3, k=0.31 and reviewer 2 vs reviewer 3, k=0.50). Conclusion: Our study demonstrates that the assessment and classification of the breast density is difficult with slightly better performance using TABAR classification system compared to BI-RADS classification. If breast density is to be used as part of risk predictors of breast cancer, a consistent, quantitative and observer-independent method for characterizing mammographic breast density is needed in local clinical practice.